Coagulation testing in acute ischemic stroke patients taking non–vitamin k antagonist oral anticoagulants - Purrucker, Jan; Rizos, Timolaos; Khan, Shujah; Veltkamp, Roland (Stroke, 2017)
Background and Purpose—In patients who present with acute ischemic stroke while on treatment with non-vitamin K antagonist oral anticoagulants (NOACs), coagulation testing is necessary to confirm the eligibility for thrombolytic therapy. We evaluated the current use of coagulation testing in routine clinical practice in patients who were on NOAC treatment at the time of acute ischemic stroke. Methods—Prospective multicenter observational RASUNOA registry (Registry of Acute Stroke Under New Oral Anticoagulants; February 2012-2015). Results of locally performed nonspecific (international normalized ratio, activated partial thromboplastin time, and thrombin time) and specific (antifactor Xa tests, hemoclot assay) coagulation tests were documented. The implications of test results for thrombolysis decision-making were explored. Results—In the 290 patients enrolled, nonspecific coagulation tests were performed in ≥95% and specific coagulation tests in 26.9% of patients.